2003
DOI: 10.1073/pnas.1933593100
|View full text |Cite
|
Sign up to set email alerts
|

ASH1, a Drosophila trithorax group protein, is required for methylation of lysine 4 residues on histone H3

Abstract: Covalent modifications of histone tails modulate gene expression via chromatin organization. As examples, methylation of lysine 9 residues of histone H3 (H3) (H3-K9) is believed to repress transcription by compacting chromatin, whereas methylation of lysine 4 residues of H3 (H3-K4) is believed to activate transcription by relaxing chromatin. The Drosophila trithorax group protein absent, small, or homeotic discs 1 (ASH1) is involved in maintaining active transcription of many genes. Here we report that in extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 25 publications
(44 reference statements)
9
105
1
Order By: Relevance
“…5C), indicating that Ash1 is an H3K36-specific dimethylase. Our results are in agreement with one previous report (20) but disagree with three other reports (19,21,22).…”
Section: H3 Premethylated At Lys-36 Inhibits Prc2-mediated Lys-27supporting
confidence: 75%
See 2 more Smart Citations
“…5C), indicating that Ash1 is an H3K36-specific dimethylase. Our results are in agreement with one previous report (20) but disagree with three other reports (19,21,22).…”
Section: H3 Premethylated At Lys-36 Inhibits Prc2-mediated Lys-27supporting
confidence: 75%
“…Thus, we decided to turn to the controversial histone methyltransferase Ash1, which is a well known Trithorax group protein that antagonizes Polycomb silencing (15,16). Although several groups reported that Ash1 is specific for H3K4 (19,21,22) or even H3K9 and H4K20 (19), one independent study reported that Ash1 is a H3K36-specific methyltransferase (20). Moreover, the Set domain of Ash1 is much more closely related to H3K36-specific methyltransferases (including HYPB and Mes4) than H3K4-specific methyltransferases such as Set1 or Trithorax (supplemental Fig.…”
Section: H3 Premethylated At Lys-36 Inhibits Prc2-mediated Lys-27mentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 26). The trithorax group is associated with "activating histone modifications" such as histone H3 Lys-4 and Lys-36 methylation (59,60) and may involve O-GlcNAcylation as part of the regulatory network (26). In general terms, the trithorax group acts as an antirepressor that counters the action of the polycomb repressive complex.…”
Section: O-glcnac and Epigenetic Regulation Of Transcription By The Hmentioning
confidence: 99%
“…Repression of homeotic gene expression is mediated by a Polycomb group (PcG) protein complex, containing Enhancer of zeste [E(Z)] and extra sex combs (ESC), that targets H3K27 and H3K9 methylation [34,35]. In contrast, the trithorax group (trxG) proteins, ASH1 [36] and Trx [37], function in targeting H3K4 methylation [38][39][40] and hence in maintaining an active state of homeotic genes.…”
Section: Introductionmentioning
confidence: 99%